Educational Technology and Student Performance: A Systematic Review - Valverde-Berrocoso, Jesús; Acevedo-Borrega, Jesús; Cerezo-Pizarro, Mario (Frontiers in Education, 2022)
The digital transformation of educational systems requires an evaluation of the effects of the integration of technologies in teaching-learning processes. From a pedagogical approach, Information and Communication Technologies (ICT) are defined, on the one hand, as the set of technologies that contain, store and disseminate information (e.g. e-books, videos or databases) and, on the other hand, those technologies designed for short-term communication (e.g. social networks, smartphones). These technologies are characterised by their tendency to merge (Hlynka, 2013). Academic achievement is one of the most widely used variables to try to understand how information and communication technologies affect student learning outcomes. Several international studies have shown little improvement in performance attributed to the use of ICT, although other reviews have shown positive results in relation to certain curricular areas. However, in general, the research is inconclusive and more studies are needed on this complex relationship. A systematic review was carried out using the Education Resources Information Center (ERIC) educational database as a documentary source, and research articles on academic performance and ICT use were selected (n=100). As a result, there was evidence of improved performance in educational practices enriched with ICT. Mathematics and science are the areas of greatest interest to researchers, and it was observed that the educational systems most oriented towards competitiveness and educational selectivity are the most productive in this field. The discrepancies between the "macro-studies" of international organizations and the "micro-studies" analyzed in this review are discussed.